2021
DOI: 10.1111/1759-7714.13832
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of SIX4 indicates poor clinical outcome and promotes tumor growth and cell metastasis in esophageal squamous cell carcinoma

Abstract: Background The role of sine oculis homeobox 4 (SIX4) has been found in some malignant tumors. However, there have been few studies on the function of SIX4 in esophageal squamous cell carcinoma (ESCC). This study aimed to explore the regulatory mechanism of SIX4 in ESCC. Methods RT‐qPCR and Western blot analysis were used to measure mRNA and protein expression. The function of SIX4 was investigated using CCK‐8, colony formation, flow cytometry, wound healing and transwell assays. A mouse xenograft tumor assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“… 17 , 18 SIX4 belongs to the sine oculis homeobox family that has been reported to be required for tumour progression, such as leukaemia, oesophageal squamous cell carcinoma, hepatocellular carcinoma and pancreatic ductal adenocarcinoma. 8 , 9 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 18 SIX4 belongs to the sine oculis homeobox family that has been reported to be required for tumour progression, such as leukaemia, oesophageal squamous cell carcinoma, hepatocellular carcinoma and pancreatic ductal adenocarcinoma. 8 , 9 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…The sine oculis homeobox 4 (SIX4) transcription factor, which belongs to the superfamily of homeobox gene family, has been identified contributes to tumour initiation, progression and metastasis 7 . For example, upregulation of SIX4 promotes tumour growth or metastasis in oesophageal squamous cell carcinoma, hepatocellular carcinoma and breast cancer 8–10 . These findings indicate that deregulation of SIX4 plays critical roles in cancer progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…SIX4 fulfills an important role in the development of multiple tumors. A previous study indicated that the upregulation of SIX4 is an indicator of poor clinical prognosis of esophageal squamous cell carcinoma, and that this leads to the promotion of tumor growth and cell metastasis ( 8 ). SIX4 is able to promote hepatocellular carcinoma metastasis via upregulation of the proteins Yes associated transcriptional regulator 1 and C-Met ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIX homeobox 4 (SIX4), a member of the homeobox family, subfamily SIX, was first found to regulate the expression of Na + /K + -ATPase subunit ( 7 ). Previous studies have demonstrated that the gene expression levels of SIX4 are closely associated with the occurrence, development, invasion, metastasis and prognosis of esophageal squamous cell carcinoma ( 8 ), breast cancer ( 9 ), bladder cancer ( 10 ), non-small cell lung cancer ( 11 ) and other tumor types, suggesting that the SIX4 gene may function as an oncogene in the development of a wide variety of tumors. In addition, a previous study has revealed that SIX4 is involved in the differentiation of epithelial follicular stem cells in the ovaries of Drosophila ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, SIX4 was identified as a downstream target of FOXA1 using a bioinformatics tool hTFtarget ( http://bioinfo.life.hust.edu.cn/hTFtarget#!/ ). SIX4 has been lately revealed to indicate dismal clinical outcome of patients with esophageal squamous cell carcinoma and to potentiate tumor growth and cell metastasis [ 11 ]. However, its role in CC, especially in regulating chemoresistance, remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%